Present Scenario and Prospect of Model Pharmacy in Dhaka City, Bangladesh (Bangladesh Pharmaceutical Journal, 2020)
The pharmaceutical sector is one of the most promising sectors of Bangladesh. With a view to elimitate the improper dispensing practice as well as matching up to the advancing global standard of health care system, the Ministry of Health and Family Welfare (MHFW), Government of the People’s Republic of Bangladesh had launched the “Model Pharmacy” program in 2016. Our aim was to find out the perception of general people regarding model pharmacy and the study the overall impact in our healthcare system due to its inauguration. A survey was conducted among the major stakeholders of model pharmacy system such as patients, physicians, retailers and DGDA personnel and the data were correlated. All the stakeholders applauded the initiative. However, each section pointed out specific problems. According to the retailers, flexibility in the license getting process was a must as they found the process to be lengthy (31.43%), unnecessarily strict (22.86%) and corrupted (22.86%). The physicians felt the program needed more exposure and recommended campaigning (23.33%). Additionally, they recommended to build up databases of doctors (46.67%) and model pharmacies (50%) for the ease of collaboration between them and the retail pharmacists. Patients were in favor of introducing more model pharmacies (20%) and recruitment of A-grade Pharmacists (6.67%). DGDA personnel noticed the miscommunication between physicians, retail pharmacists and authority to be a major problem. All the stakeholders unanimously focused on regular monitoring of the program to make it a success. Beyond this discussion, we are hopeful that with adequate measures and continuous modification, the “Model Pharmacy” program would become successful in Bangladesh.Bangladesh Pharmaceutical Journal 23(2): 172-180, 2020